Seed bank persistence of artificial vegetation under stochastic shock in desert regions. (December 2021) - Fu, Tonglin; Li, Xinrong; Jia, Rongliang
Highlights: A stochastic shock model is proposed to investigate seed banks persistence. The lower bound of the probability of seed bank persistence under stochastic shocks is presented. The seed bank persistence of artificial sand-binding vegetation was investigated. Abstract: Seed bank persistence plays a significant role in maintaining the sustainability of artificial vegetation in desert regions. However, the periods of droughts after each rainfall event form a series of stochastic shocks and result in depletion of the seed bank. Understanding seed bank persistence under stochastic shocks is a crucial prerequisite to evaluation of the sustainability of artificial vegetation under ongoing drought, but few studies have addressed the response of soil seed bank persistence to frequent stochastic shocks in deserts. In this paper, a stochastic shock model describing the input–output process of the seed bank is proposed based on modern risk theory to explore seed bank persistence of artificial vegetation in desert regions. The existence condition of the seed bank and the lower bound of the probability of seed bank persistence under stochastic shock after a long time were theoretically determined. As a verification of the theoretical model, seed bank persistence of artificial sand-binding vegetation on the southeastern margin of the Tengger Desert in China was investigated based on field observation and experimental and empirical data. The numerical results reveal that the seed bank of artificial sand-binding vegetation will always exist under stochastic shocks with a probability greater than 95%, suggesting that in the long-term succession process the current artificial sand-binding vegetation will likely maintain the development trend toward the adjacent natural vegetation.